Child Abuse and Neglect in Uganda - Kaawa-Mafigiri, David; Walakira, Eddy Joshua (Springer International Publishing : Imprint: Springer, 2017)
This book provides a unique perspective on addressing issues of various forms of violence against children from scholars within their own country. Bringing together cross-disciplinary expertise, this volume addresses a vast range of topics related to child abuse and neglect in Uganda. Exploring areas from the protection of street children to cultural proverbs related to child maltreatment, this volume examines issues both specific to the Ugandan contexts as well as broadly experienced in child maltreatment work in non-Euro-American countries. This book surveys the breadth of the child protection field, covering issues of children's universal rights, challenges of protection and ethical quandaries in researching and addressing maltreatment.
Keywords: Social sciences.; Maternal and child health services.; Human rights.; Social work.; Childhood.; Adolescence.; Social groups.; Well-being.; Children.; elektronické knihy; electronic books